Restoring Abandoned Agricultural Lands in Cold Desert Shrublands: Tradeoffs between Water Availability and Invasive Species - Chambers, Jeanne C.; Eldredge, Eric P.; Snyder, Keirith A.; Board, David I.; Forbis de Queiroz, Tara; Hubbard, Vada (Invasive plant science and management, 2014)
Restoration of abandoned agricultural lands to create resilient ecosystems in arid and semi-arid ecosystems typically requires seeding or transplanting native species, improving plant–soil–water relations, and controlling invasive species. We asked if improving water relations via irrigation or surface mulch would result in negative tradeoffs between native species establishment and invasive species competition. We examined the effects of sprinkler irrigation and straw mulch on native seed mixtures planted in two consecutive years in an abandoned agricultural field in a cold desert shrubland in southwestern Nevada, USA. Restoration effects differed among years because of contingency effects of growing season conditions. Precipitation was low during the first year and seeded plant density and biomass increased in response to irrigation. Precipitation was relatively high during the second year, seeded plant densities and biomass were generally high, and irrigation had inconsistent effects. Mulch increased native plant cover in the absence of irrigation during the dry year. Invasive plant biomass and cover also were influenced by year, but irrigation increased invasive plants regardless of precipitation. Positive effects of irrigation on seeded plant density, cover, and biomass outweighed negative tradeoffs of increases in invasive plants. In ecosystems with highly variable precipitation, the most effective restoration strategies will most likely be adaptive ones, requiring determination of timing and amount of irrigation based on precipitation, native plant establishment, and invasive species composition and abundance. Nomenclature: 2, 4-D; dimethylamine salt of 2,4-dichlorophenoxyacetic acid. Management Implications: Restoration of abandoned agricultural land to native plant communities can increase soil stability, reduce the spread of invasive species, and enhance the conservation value of the land. In cold desert shrublands where irrigation systems are still in place, irrigation can promote native species establishment despite also increasing invasive species. Irrigation must be sufficiently frequent during initial establishment of the seeded species to maintain the soil drying front above the depth of active root growth. Periodic watering may be required through the second year to allow plants to survive the generally low precipitation and highly variable weather conditions that characterize cold desert shrublands. In cases where irrigation systems are not available, mulch may be a viable alternative for improving water relations and increasing plant cover, especially during dry years. Larger seeded species, such as the grasses Indian ricegrass, squirreltail and needle and thread are likely to establish at higher rates than smaller seeded species like sagebrush and many native forbs. Flexible restoration strategies that adapt the timing and amount of irrigation to soil water availability are most likely to succeed.